Revitalizing Residential Alleys through Urban Farming-Based Herbal Plant Cultivation in Sukoharjo Regency - Sudiarti Dewi Dewi; Nurul Aliah; Ahmad Wahidiyat Haedar; Moeh Kay Muddin Asnu; Ahnaf Ryandirga Putra Helmy (Universitas Negeri Makassar, 2026)
The limited green space in densely populated residential areas often results in the emergence of slum-like, poorly organized alleys with minimal productive use of space. This problem was found on Jl. Pramuka Dukuh Bacem, Grogol District, Sukoharjo Regency, which has residential alleys with minimal vegetation and lack of environmental aesthetic value. This community service activity aims to revitalize residential alleys through urban farming-based herbal plant cultivation with a vertical system using recycled planting media. The implementation method is carried out through the stages of site observation, problem identification with partners, planning herbal plant installations, preparation of tools and materials, installation of vertical planting media, planting herbal plants, and program evaluation based on community surveys. The herbal plants used include lemongrass, mint, betel, basil, and aloe vera, which were selected based on their ease of care and benefits to the community. The results of the activity showed a significant change in the environmental condition of the alleys, which previously looked slum-like to become greener, cleaner, and more aesthetic. In addition to improving the visual quality of the environment, this program also increased community participation in maintaining cleanliness and the productive use of narrow spaces. Evaluation results for 12 households showed improvements in environmental cleanliness, the presence of green vegetation, road user comfort, and community use of herbal plants. This program demonstrates that implementing herbal-based urban farming can be a simple and sustainable solution for revitalizing densely populated residential areas.